Antisocial behavior in students and homeless children: Influence of neighborhood and parents - Banda Castro, Ana Lilia (2006)
The aim of this work was to analyze the influence of neighbors and parents on children’s antisocial behavior. The participants were 96 homeless children and 96 students. The instruments applied were the Scale of Antisocial Behavior (Castell, Frías, Corral & Sotomayor, 2000) and the Scales of Addictive Behavior (Reich & Herjanic, 1989; Vazsonyi, Pickering, Junger & Hessing, 2001). First univariate statistics were obtained, after a model was tested using structural equations modeling. The data showed that children’s antisocial and addictive behavior was affected by father’s antisocial behavior, mother’s addictive behavior and neighborhood. For homeless children their antisocial behavior was influenced directly by their addictive behavior and father’s antisocial behavior. For students, neighborhood, father’s antisocial behavior and children’s addictive behavior influenced on children’s antisocial behavior. In both groups the neighborhood and mother’s addictive behavior influenced directly children’s addictive behavior.